Adaptation of the International Fitness Scale and Self-Perceived Health-Related Physical Fitness Questionnaire into Turkish - Tuba İnce Parpucu; Görkem Kıyak; Fatih Uğur Taş; Mert Usta; Aydan Örsçelik; Sabriye Ercan (Children, 2023)
This study aims to investigate the Turkish validity and reliability of the International Fitness Scale (IFIS) and the Self-Perceived Health-Related Physical Fitness Questionnaire for Children (SPHQ-C) aged 10–17. The measurement tools were translated into Turkish by two independent researchers and back-translated. Then, the content validity was established with a group of 13 individuals (Sample 1) who presented to the sports medicine clinic. The pilot application phase was initiated. A sample of 372 individuals (Sample 2) studying in the provincial center was selected for piloting the measurement tools with the ALPHA-FIT Test Battery. The test–retest application of the measurement tools with a 15-day interval was carried out with 207 individuals (Sample 3) not included in Sample 2. The authors calculated that the content validity ratio values for the items in the IFIS ranged from 0.85 to 1.00, with a content validity index of 0.94 for the scale. In the SPHQ-C, these values were found to be between 0.92 and 1.00, with a content validity index of 0.99. According to the Z-score difference analysis for both measurement tools, the construct validity of all items was achieved (p < 0.05). In the Bland–Altman plot test conducted for the IFIS-TR, the mean difference was calculated as 0.11, the standard deviation of the differences was 1.57, and the p-value was determined as 0.31. For the SPHQ-C-TR, the mean difference was −0.15, the standard deviation of the differences was 1.95, and the p-value was determined as 0.26. The Kappa coefficients for the items of the IFIS-TR ranged from 0.45 to 0.52, while for the SPHQ-C-TR, the Kappa coefficients ranged from 0.47 to 0.75. Confirmatory factor analysis conducted on Sample 2 confirmed model fit indices with covariance among some items of the measurement tools (IFIS-TR: e1–e3; SPHQ-C-TR: e1–e2, e1–e3, e2–e3, e3–e4, e6–e7, e8–e9). The IFIS and SPHQ-C measurement tools have been adapted into Turkish, and their validity and reliability have been established.